The Cognitive Diagnostic Assessment in Learning to Write Personal Letters in Elementary School - heri, heri prihartono; Rustam (Institut Agama Islam Negeri Palopo, 2024)
A cognitive diagnostic assessment is a process of gathering information to identify students' strengths and weaknesses in cognitive aspects. In the context of teaching personal letter writing in elementary school, a cognitive diagnostic assessment can help teachers understand students' initial comprehension of the structure and elements of personal letters. The purpose of this research is to determine students' abilities in critical thinking, reasoning, and problem-solving, as well as to assess their readiness for learning. This research employs a qualitative approach with a case study method to explore how teachers implement, evaluate, and assess the outcomes of cognitive diagnostic assessments in teaching personal letter writing at SD Batanghari. The study reveals that cognitive diagnostic assessments can assist teachers in achieving the desired learning objectives and enhance teachers' insights regarding diagnostic assessments. The findings also indicate that cognitive diagnostic assessments can be used to map students' learning needs based on their learning styles, interests, and skills. Cognitive diagnostic assessments in teaching personal letter writing in elementary school play a crucial role in ensuring that students can complete tasks well and achieve the expected learning goals. Thus, this research contributes to the development of cognitive assessments that are aligned with the core material and can improve students' problem-solving abilities in elementary school.